Expectant parents' perspectives on the influence of a single antenatal relaxation class: A qualitative study. (May 2021) - Tabib, Mo; Humphrey, Tracy; Forbes-McKay, Katrina; Lau, Annie
Abstract: Aim: This study explores the perspectives of expectant parents on the influence of a single antenatal class incorporating education on childbirth physiology and relaxation techniques. Method: The data for this qualitative descriptive study were collected via in-depth interviews with six women and three birth partners. Findings: An enhanced understanding of childbirth physiology formed a ' different way of thinking ' about childbirth, ' inspired and motivated' the exertion of the learnt relaxation techniques which led to a ' deep sense of calmness' associated with increased confidence and reduced fear. However, reaching such sense of calmness during childbirth required a ' space for relaxation ' which was influenced by birth attendants. An overarching theme of 'a positive outlook' towards childbirth was identified. Conclusion: Including education on childbirth physiology and a range of relaxation techniques may reduce fear, empower prospective parents and positively influence their experiences of pregnancy and childbirth. Highlights: Understanding the childbirth physiology alleviates fear and inspires an active role. Effectiveness of relaxation techniques during childbirth depends on practitioners' attitudes. Antenatal relaxation classes may enhance overall maternal sense of wellbeing. Antenatal relaxation classes may help women perceive childbirth experience as positive.